Short-term malnutrition in Wistar rats - Malafaia, Guilherme; Guimarães, Abraão Tiago Batista; Lemes, Camila Gracyelle de Carvalho; Estrela, Dieferson da Costa (Scientia Plena, 2014)
The aim of the present study is to evaluate the effects of short-term malnutrition on physical, biochemical, hematological and histological parameters in Wistar rats. Ninety day-old female rats were submitted to food restriction by adopting a diet containing 6% protein. The animals of the control group were fed with a standard commercial diet containing 19% protein. After malnutrition (indicated by differences in body mass) was established, the rats were euthanized and the absolute and relative masses of liver, spleen, heart, pancreas, brain, kidneys, lungs and adrenal glands, and biochemical and hematological parameters were analyzed, as well as the histology of the spleen, liver and kidneys. The malnutrition group presented lower concentrations of leukocytes, triglycerides and very-low-density lipoproteins (VLDL), and higher relative liver mass, with incipient histopathological changes, when compared to those obtained for the control group. These data suggest that short-term malnutrition is able to induce a malnutrition condition and signs of liver alteration, but it does not cause generalized biochemical and hematological changes.